Hypnotherapy and Hypnosis - Mordeniz, Cengiz (IntechOpen, 2020)
Although hypnosis has been used for centuries to improve mental health and well-being, not until recently has it been applied in modern medicine. Some efforts to integrate hypnosis into Western medical practice in the late nineteenth century were met with stiff resistance by the majority of medical doctors due to lack of scientific foundation, thus hampering its widespread use. The biopsychosocial approach brought about by recent progress in brain research, however, has revived the interest in hypnotherapy. In this book, we shed light on the scientific basis of hypnosis and elaborate its use in modern medical practice.